Association of Preoperative Plasma D-Dimer and Fibrinogen and Osteosarcoma Outcome - Pu, Yanchuan; Wang, Jin; Wang, Jianshu; Wang, Shizhong (Frontiers in Oncology, 2022)
Objective We aimed to evaluate the utility of preoperative D-dimer and plasma fibrinogen (PF) levels as useful markers for predicting the clinical value of patients with osteosarcoma. Methods 145 enrolled patients with osteosarcoma were studied retrospectively. We determined the critical values of D-dimer and PF by receiver operating characteristic curve analysis. Cox regression analysis was used to assess prognostic role of the D-dimer and PF levels among osteosarcoma patients. Results The critical values of D-dimer and PF were calculated to be 0.46 µg/mL and 3.34 mg/mL, respectively. Upregulation of D-dimer and PF showed positive correlations with a higher clinical stage, tumour metastasis and recurrence. Survival curve results confirmed that osteosarcoma patients with higher levels of D-dimer and PF predicted worse overall survival (OS) and progression-free survival (PFS). Moreover, only a high D-dimer level was associated with a shorter OS (P = 0.013) and PFS (P = 0.042) in both the univariate and multivariate analysis. Conclusion Elevated preoperative D-dimer levels are correlated with aggressive clinicopathological features and poor survival outcomes, which indicates that assessment of the D-dimer could be a useful prognostic marker in osteosarcoma.